A novel MED12 mutation: Evidence for a fourth phenotype. Issue 9 (17th June 2016) - Prontera, Paolo; Ottaviani, Valentina; Rogaia, Daniela; Isidori, Ilenia; Mencarelli, Amedea; Malerba, Natascia; Cocciadiferro, Dario; Rolph, Pfundt; Stangoni, Gabriela; Vulto‐van Silfhout, Anneke; Merla, Giuseppe
Abstract : Mutations of the MED12 gene have been reported mainly in males with FG (Opitz–Kaveggia), Lujan–Fryns, or X‐linked Ohdo syndromes. Recently, a different phenotype characterized by minor anomalies, severe intellectual disability (ID), and absent language was reported in female and male patients belonging to the same family and carrying a frameshift MED12 mutation (c.5898dupC). Here, we report on two brothers and their niece affected by severe and mild ID, respectively, where whole exome sequencing combined with variant analysis within a panel of ID‐related genes, disclosed a novel c.2312T>C (p.Ile771Thr) MED12 mutation. This variant, which has not been reported as a polymorphism, was not present in a third unaffected brother, and was predicted to be deleterious by five bioinformatic databases. This finding together with the phenotypic analogies shared with the carriers of c.5898dupC mutation suggests the existence of a fourth MED12 ‐related disorder, characterized by severe ID, absent or deficient language and, milder, clinical manifestation in heterozygotes. We have reviewed the literature on MED12 heterozygotes, their clinical manifestations, and discuss the possible biological causes of this condition. © 2016 Wiley Periodicals, Inc.